Kondisi Sanitasi Mesjid di Wilayah Desa Kejapanan Kabupaten Pasuruan - Alindia, Hiska Tri Ulan; Hermiyanti, Pratiwi; Winarko, Winarko; Rusmiati, Rusmiati; Rachmaniyah, Rachmaniyah (Poltekkes Kemenkes Palembang, 2023)
ABSTRACT Background: The mosque in Kejapanan Village, Pasuruan Regency has sanitation problems in the form of inadequate physical buildings. Based on a preliminary survey, there was 1 mosque using well water which had an E.Coli content of 650 compared to the required level of 0/100 ml. The aim of this research is to describe the sanitary conditions of mosques in the Kejapanan Village area, Pasuruan Regency. Method: The design of this research is descriptive observational research, with a cross-sectional approach. The variables studied included the sanitary conditions of mosques and E.Coli parameters of well water in the Kejapanan Village area, Pasuruan Regency. Data collection techniques use observation. The data collected was then analyzed descriptively through table analysis. Results: Mosque sanitation assessments have been carried out, in the 4 mosques in Kejapanan Village, Pasuruan Regency, there are still mosques that do not meet the requirements. The mosque studied did not have facilities such as prayer carpets and trash cans with lids. Mosque well water samples tested by the UPTD Regional Health Laboratory, resulted in an Escherichia coli (E.Coli) content of 25 - 650 from a maximum level of 0/100 ml so it did not meet clean water quality standards. Conclusion: Mosque sanitation in Kejapanan Village, Pasuruan Regency, there are still mosques that do not comply with sanitation requirements. For mosque managers, efforts need to be made to improve mosque sanitation and for future researchers, they can carry out research using input variables that are thought to cause contamination of mosque sanitation and sources of clean water for ablution in mosques. Keywords: Mosque Sanitation, Well Water Microbiology